Lack of association between serotonin transporter gene polymorphism 5-HTTLPR and smoking among Polish population: a case-control study - Jassem Ewa; Buczkowski Krzysztof; Sieminska Alicja; Tkacz Ewa (BMC, 2008)
Abstract Background A better understanding of the genetic determinants of tobacco smoking might help in developing more effective cessation therapies, tailored to smokers' genotype. Insertion/deletion polymorphism in the promoter region of the serotonin transporter gene (5-HTTLPR) has been linked to vulnerability to smoking and ability to quit. We aimed to determine whether 5-HTTLPR genotype is associated with smoking behavior in Caucasians from Northern Poland and to investigate other risk factors for tobacco smoking. Methods 5-HTTLPR genotypes were determined in 149 ever smokers (66 females; mean age 53.0 years) and 158 gender and ethnicity matched never smoking controls (79 females; mean age 45.0 years) to evaluate the association of this polymorphism with ever smoking status. Analysis of smokers was performed to evaluate the role of 5-HTTLPR in the age of starting regular smoking, the number of cigarettes smoked daily, pack-years, FTND score, duration of smoking, and the mean length of the longest abstinence on quitting. Genotype was classified according to the presence or absence of the short (S) allele vs. the long (L) allele of 5-HTTLPR (i.e., S/S + S/L vs. L/L). Logistic regression analysis was also used to evaluate correlation between ever smoking and several selected variables. Results We found no significant differences in the rates of S allele carriers in ever smokers and never smokers, and no relationship was observed between any quantitative measures of smoking and the polymorphism. Multivariate analysis demonstrated significant association between the older age (OR = 4.03; 95% CI: 2.33-6.99) and alcohol dependence (OR = 10.23; 95% CI: 2.09-50.18) and smoking. Conclusion 5-HTTLPR seems to be not a major factor determining cigarette smoking in Poles. Probably, the risk of smoking results from a large number of genes, each contributing a small part of the overall risk, while numerous non-genetic factors might strongly influence these genetic undergrounds of susceptibility to smoking.